1991
DOI: 10.1165/ajrcmb/5.5.416
|View full text |Cite
|
Sign up to set email alerts
|

Pneumolysin Induces the Salient Histologic Features of Pneumococcal Infection in the Rat Lung In Vivo

Abstract: Streptococcus pneumoniae infections are common, but how they cause host tissue injury and death is incompletely understood. Immunization with pneumolysin, a thiol-activated toxin produced by the pneumococcus, partially protects animals during subsequent infection. The mechanism by which pneumolysin contributes to disease is not known. The aim of the present investigation was to determine the histologic changes induced by recombinant pneumolysin in the rat lung and to compare them with the changes induced by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 34 publications
3
54
0
1
Order By: Relevance
“…Ply-deficient strains of S. pneumoniae are attenuated in animal models of pneumonia and sepsis (13). In addition, purified toxin is sufficient to induce many of the features of pneumococcal lung disease, including neutrophil recruitment, just as it recapitulated the effect of whole S. pneumoniae in our experiments (39). Here, we demonstrate that Ply is necessary and sufficient for the pneumococcal contribution to synergistic epithelial activation, an effect that is independent of TLR4 (18).…”
Section: Discussionsupporting
confidence: 66%
“…Ply-deficient strains of S. pneumoniae are attenuated in animal models of pneumonia and sepsis (13). In addition, purified toxin is sufficient to induce many of the features of pneumococcal lung disease, including neutrophil recruitment, just as it recapitulated the effect of whole S. pneumoniae in our experiments (39). Here, we demonstrate that Ply is necessary and sufficient for the pneumococcal contribution to synergistic epithelial activation, an effect that is independent of TLR4 (18).…”
Section: Discussionsupporting
confidence: 66%
“…The importance of pneumolysin as a pneumococcal virulence factor was reported in several in vivo studies that showed reduced pathogenesis in mice infected with pneumolysin-deficient strains of S. pneumoniae compared with isogenic toxin-producing strains (27)(28)(29)(30). Furthermore, application of purified pneumolysin directly into the lungs of rats induced an acute inflammatory response similar to that observed during pneumococcal pneumonia (31).…”
mentioning
confidence: 73%
“…A leading candidate for such a protein-based vaccine is pneumolysin (PLY) 3 : it is an important virulence factor of S. pneumoniae (11,12), is highly conserved across all serotypes (13), is immunogenic in humans (14,15), and has shown protection in numerous animal models of infection (16 -18). However, PLY is a toxin that oligomerizes to form large pores in the membranes of target host cells (19).…”
mentioning
confidence: 99%